COVID-19 and the need to recognize infectologists and infectious disease services as key elements of the health system (Actualizaciones en Sida e Infectología, 2021)
More than a year after the pandemic, we continue to reflect on what we have learned so that we can be better prepared to face similar situations in the future.During 2020, social, preventive and mandatory isolation had a significant impact on the lives of all people.In the article by Radusky et al. included in this issue we see how, during the first months of the pandemic, belonging to a risk group was associated with greater compliance with preventive measures, although greater compliance was also associated with greater anxiety and, at times, depression (1). It was in this context that SADI proactively took the decision to communicate the situation in a responsible manner, with clear messages, without low blows and respectfully, so that the community could learn about the disease and take measures to take care of themselves.We believe we have met this goal based on the activities we completed during 2020: over 4,000 journalistic interviews, more than 80 virtual meetings, a strong presence on social networks and a virtual congress in which almost 8,000 people participated.Moreover, since the beginning of the pandemic, infectologists in most institutions have assumed the responsibility of reviewing the evidence, establishing protocols, organizing care circuits, training human resources, participating in patient care and supporting clinical research in order to rapidly develop new prevention and treatment options.The call to SADI to advise all government agencies is also a recognition of the importance of infectious diseases.The medical literature clearly demonstrates that the presence of infectious disease specialists produces better clinical outcomes in patients, optimizes resources, reduces the cost of care and mitigates the impact of antimicrobial resistance (Table 1).However, there is still a long way to go to achieve a fair recognition of the specialty and the consequent higher status of the specialists who practice it.In our country, there are many hospitals and sanatoriums that serve a very large volume of patients.In many of them, major surgeries are performed within intensive care units and complex pathologies are treated without infectious disease specialists hired on a stable basis, whose workload is insufficient to solve all the institutional complexity and who work within services or structures that are not recognized as infectology services.This scenario is repeated in the public, private and social security sectors.Such a situation deprives patients, institutions and the community of the benefits that these specialized services have proven to provide, and which make their presence essential.Preliminary results of a survey conducted among 173 infectologists in Argentina, working in 181 centers in 20 provinces, showed that only half of the institutions have recognized infectology services, this percentage being as low as 40% in public institutions and 70% in private ones, with no substantial differences between the different districts.The same survey showed that the average specialists to beds ratio is 1/67.9 beds, but reaches a ratio of 1/300 beds in some institutions (2).In view of the above, it is evident that having a sufficient number of infectious disease specialists for the number and complexity of patients served, in addition to prioritizing their work by creating institutional structures in accordance with the particular practices of each organization, is a minimum standard that should be guaranteed in all healthcare centers in the country. In that respect, few weeks ago, SADI published a document analyzing these points (3).Covid-19 brought to everyone's attention the reality and the deficits in health services, forcing public, private and social security providers to suddenly organize those services for the contingency of an unknown disease of pandemic magnitude.In the same way, we were able to strengthen the health system, design care programs, implement surveillance, carry out epidemiological containment actions and develop a major vaccination program.Although "what is urgent is seldom important and what is important is seldom urgent" is often a popular saying, let's hope that "what is important" starts to become a necessity in public opinion and on the health policy agenda.The possibility of eliminating HIV as a public health problem, the increase in sexually transmitted infections, the increasing challenge of bacterial resistance and the few options available, diseases that should be under control, such as tuberculosis and other endemic pathologies, and the ever present risk of new pandemics force us to demand full acknowledgement of the need for infectious disease services in all institutions, with well-trained professionals, with decent salaries, hired on a stable basis and with the necessary resources to carry out their daily task.This is an imperative social need, a sign of intelligence from those who make health care decisions, and an unavoidable demand from scientific communities. Dr. Omar Sued Fundación HuéspedSADI’s former Chairperson  Dr. Pablo Scapellato Hospital SantojanniBoard of Directors, SADI